2011
DOI: 10.1167/iovs.10-6061
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Corneal Astigmatism in Tohono O'odham Native American Children 6 Months to 8 Years of Age

Abstract: The prevalence and mean amount of corneal astigmatism were higher than reported in non-Native American populations. Mean astigmatism increased from 1.43 D in 1-year-olds to nearly 2.00 D by school age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…[9][10][11][12] Recent reports of data from Tohono O'odham infants show a high prevalence of astigmatism, which decreases in the second year of life. 12,13 This pattern is similar to that seen in Caucasian, Asian, and Hispanic infants: astigmatism is prevalent in infancy, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] but longitudinal studies indicate that the amount of astigmatism decreases significantly after the first year of life. 17,18,21,23,[28][29][30][31] However, cross-sectional data has shown that the initial decrease in prevalence of astigmatism after infancy in Tohono O'odham children is followed by an increase in prevalence by age 2 years to the level we see in Tohono O'odham preschool and school-age children.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…[9][10][11][12] Recent reports of data from Tohono O'odham infants show a high prevalence of astigmatism, which decreases in the second year of life. 12,13 This pattern is similar to that seen in Caucasian, Asian, and Hispanic infants: astigmatism is prevalent in infancy, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] but longitudinal studies indicate that the amount of astigmatism decreases significantly after the first year of life. 17,18,21,23,[28][29][30][31] However, cross-sectional data has shown that the initial decrease in prevalence of astigmatism after infancy in Tohono O'odham children is followed by an increase in prevalence by age 2 years to the level we see in Tohono O'odham preschool and school-age children.…”
Section: Introductionsupporting
confidence: 61%
“…17,18,21,23,[28][29][30][31] However, cross-sectional data has shown that the initial decrease in prevalence of astigmatism after infancy in Tohono O'odham children is followed by an increase in prevalence by age 2 years to the level we see in Tohono O'odham preschool and school-age children. 12,13 The purpose of the present study was to longitudinally examine change in corneal astigmatism in infants and young Tohono O'odham children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of childhood astigmatism decreases with age (1,2,15,18,19); according to a longitudinal study, the most outstanding changes in the rate of astigmatism occur between the first and the second year of life, 1 and further decrease can be detected up to 6 years (1) and after (2,3). Other studies do not confirm such age-adjusted changes in children in various populations (13).…”
Section: Discussionmentioning
confidence: 82%
“…The second most prevalent type was ATR in some studies (the present study and the study by Xiao et al (22)), and oblique in some other studies (10,21,23). Age-related astigmatism axis change has been reported in various populations; this has been attributed to decreased lid tension, corneal flattening and rotation of the horizontal axis to the vertical orientation (6,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 50%